2020
DOI: 10.1159/000507714
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>NT5C2</i></b> Gene Polymorphisms and the Risk of Coronary Heart Disease

Abstract: Background: Increasing studies have reported that 5′-nucleotidase cytosolic II (NT5C2) has a strong relationship with coronary heart disease (CHD) development. This study was designed to examine the relationship between NT5C2 polymorphisms and CHD in the Chinese Han population. Methods: We studied 501 CHD patients and 496 healthy controls from the Second Affiliated Hospital of Hainan Medical University in Hainan Province, China. Four single nucleotide polymorphisms (SNPs) in NT5C2 were selected and genotyped u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…At the same time, these three SNPs increased the risk of CHD in patients aged 62 years and younger and smokers. These results are consistent with previous studies indicating that genetic polymorphisms influence the susceptibility to CHD in males or patients aged ≤61 years ( 29 , 30 ). Zhao et al ( 31 ) found that the morbidity and mortality of cardiovascular diseases were correlated with the degree of blood pressure elevation.…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, these three SNPs increased the risk of CHD in patients aged 62 years and younger and smokers. These results are consistent with previous studies indicating that genetic polymorphisms influence the susceptibility to CHD in males or patients aged ≤61 years ( 29 , 30 ). Zhao et al ( 31 ) found that the morbidity and mortality of cardiovascular diseases were correlated with the degree of blood pressure elevation.…”
Section: Discussionsupporting
confidence: 93%
“…CHD is a kind of multifactorial disease resulting from environmental and genetic factor. An increasing number studies strongly supported that genetic polymorphisms involve in the risk of CHD, such as SCARB1 [ 26 ], RTEL1 [ 27 ], 5- HTTLPR [ 28 ], CD40 [ 29 ], and NT5C2 [ 30 ]. The CYP7B1 gene is located on chromosome 8q21.3.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, Zhang et al and Ye et al reported that genetic polymorphism influence CHD risk in age > 60 years and age > 65 years [ 31 , 32 ]. However, Huang et al and Chen et al showed that gene variants are associated with the susceptibility to CHD in age ≤ 61 years [ 30 , 33 ]. Age is a risk factor for CHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPP1R3G is downregulated in the liver by fasting and increased by feeding, and it plays an important role in the control of postprandial glucose homeostasis through its regulation of hepatic gluconeogenesis during the fasting–feeding transition [ 43 ]. The 5′-nucleotidase cytosolic II (NT5C2) variants were reported to be nominally associated with coronary heart disease (CHD) susceptibility in the subgroups of males and with hypertension and diabetes [ 44 ]. Ubiquitin-specific protease 15 (USP15) was found to be a potential target of miR-26a and mediated the proautophagic and cardioprotective effects of miR-26a against ischemic injury [ 45 ].…”
Section: Discussionmentioning
confidence: 99%